Wpływ eventów sportowych na rozwój turystyki w mieście na przykładzie poznańskich imprez sportowych = The impact of sporting events on tourism development in the city - the case study of Poznan - Poczta, Joanna; Malchrowicz-Mośko, Ewa (Journal of Education, Health and Sport, 2016)
Poczta Joanna, Malchrowicz-Mośko Ewa. Wpływ eventów sportowych na rozwój turystyki w mieście na przykładzie poznańskich imprez sportowych = The impact of sporting events on tourism development in the city - the case study of Poznan. Journal of Education, Health and Sport. 2016;6(4):151-166. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50021 http://ojs.ukw.edu.pl/index.php/johs/article/view/3459 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016. Wpływ eventów sportowych na rozwój turystyki w mieście na przykładzie poznańskich imprez sportowych The impact of sporting events on tourism development in the city - the case study of Poznan Joanna Poczta, Ewa Malchrowicz-Mośko Zakład Kulturowych Podstaw Turystyki Wydział Turystyki i Rekreacji / AWF w Poznaniu Dr Joanna Poczta, Mgr Ewa Malchrowicz-Mośko Zakład Kulturowych Podstaw Turystyki Wydział Turystyki i Rekreacji / AWF w Poznaniu Słowa kluczowe: eventy sportowe, turystyka sportowa Key words: sport events, sport tourism Streszczenie Artykuł prezentuje wyniki badań empirycznych przeprowadzonych w Poznaniu podczas trwania trzech ważnych wydarzeń sportowych: 6. Poznań Półmaratonu, „Cavaliady” (zawody jeździeckie) oraz Mistrzostw Europy Juniorów w Pływaniu. Postanowiono sprawdzić, które z wydarzeń generuje największy ruch turystyczny w badanej metropolii. Artykuł wskazuje również, jakie zachowania w czasie podróży przejawiają zarówno sportowcy, jak i kibice badanych wydarzeń sportowych. Celem badań była próba wykazania, w jakim stopniu uczestnicy wydarzeń sportowych (zawodnicy oraz kibice) podejmują dodatkową aktywność turystyczną w mieście przy okazji udziału w zawodach sportowych (zakupy, wyjście do restauracji itp.) oraz czy ranga sportowa imprezy wpływa na częstotliwość tych zachowań i czy turystyka sportowa sprzyja rozwojowi innych form turystyki, np. turystyki kulturowej (wizyta w muzeum, udział w evencie kulturalnym itp.). Analiza zebranych danych pokazała, że odbywające się w Poznaniu imprezy mają wpływ na rozwój turystyki w mieście. Jednak te wydarzenia, które mają niższą rangę sportową, generują większy ruch turystyczny. Im wyższa ranga imprezy tym bardziej sportowcy i ich kibice koncentrują się na zawodach i rywalizacji. Okazuje się też, że im mniej ciekawych rzeczy dzieje się na zawodach, tym częściej kibice poszukują alternatywnych form zagospodarowania czasu wolnego i mają one większy wpływ na rozwój innych form turystyki– na przykład turystyki kulturowej. Jeżeli zatem władzom zależy na rozwoju turystyki miejskiej, to powinny częściej organizować imprezy z zakresu sportu masowego. Poznań ma duży potencjał do dalszego rozwoju turystyki sportowej, a ta pozytywnie wpływa też na budowanie wizerunku miasta, kształtowanie postaw turystów i mieszkańców wobec zdrowia i aktywności fizycznej, a przede wszystkim pokazuje miasto jako atrakcyjne turystycznie, z ciekawą ofertą kulturalną i rozrywkową. Abstract The article presents the results of empirical research conducted in Poznan during the three major sporting events: 6. Poznan Half Marathon, "Cavaliada" and the European Junior Swimming Championships. It was decided to see which event generate the highest tourist traffic in the studied city. Article also indicates what kind of tourism behaviors exhibit both athletes and fans during sporting event competition. The aim of the study was to demonstrate the extent to which participants in sporting events (players and fans) take additional tourist activity in the city on the occasion of participation in sports competitions (shopping, going to restaurants, etc.) The highest rank of sporting event the stronger effect on the frequency of these behaviors, and whether sports tourism promotes the development of other forms of tourism, for example cultural tourism (visit to the museum, participation in a cultural event, etc.). Analysis of the collected data shows that the organization of sporting events in Poznan affect the development of tourism in the city. However, these events, which have a lower sport rank, generate more tourist traffic. The higher the rank the more events athletes and their fans are focused on competition and rivalry. It also turns out that the less interesting things going on in the competition, the more the fans are looking for alternative forms of leisure time activities and have a greater impact on the development of other forms of tourism - such as cultural tourism. Therefore, if the authorities depends on the development of urban tourism, it should organize more events in the field of mass sports. Poznan has a high potential for further development of sport tourism, and it has also a positive effect on building the image of the city, shaping the attitudes of tourists and residents to the health and physical activity, and above all shows the city as an attractive tourist destination with interesting cultural offer and entertainment.